THE THE INFLUENCE OF THE SCRIPT TYPE COOPERATIVE LEARNING MODEL ON THE SCIENCE LEARNING OUTCOMES OF CLASS V STUDENTS OF SDN 15 BUNGKU - _, Rusdin; _, Misnah; Ratu, Bau; _, Juraid; _, Iskandar (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
The problem of this research is the low social studies learning outcomes of students in class V at SDN 15 Bungku due to the lack of teacher creativity in implementing learning. Teachers only rely on conventional methods by means of lectures, even though there are many methods that can be used to motivate students to learn so that their learning outcomes increase. One method that can be used is script type cooperative learning. The aim of this research is to determine the effect of using the script type cooperative learning method on students' social studies learning outcomes. Method (quasi experiment) with a nonequivalent control group design research design. Class V sample with a total of 33 students. Consisting of 17 people in the experimental group and 16 people in the control group. With a sample collection technique, namely purposive sampling. Observation data collection techniques as well as pretest and posttest. Data analysis techniques use the t test. Based on the results of the T-test calculations, it was concluded that there was a significant influence of the use of the Script Type Cooperative Learning model on the social studies learning outcomes of class V students at SDN 15 Bungku.